2011
DOI: 10.1098/rstb.2010.0331
|View full text |Cite
|
Sign up to set email alerts
|

Community genetics: what have we accomplished and where should we be going?

Abstract: Research in community genetics seeks to understand how the dynamic interplay between ecology and evolution shapes simple and complex communities and ecosystems. A community genetics perspective, however, may not be necessary or informative for all studies and systems. To better understand when and how intraspecific genetic variation and microevolution are important in community and ecosystem ecology, we suggest future research should focus on three areas: (i) determining the relative importance of intraspecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
118
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 101 publications
(118 reference statements)
3
118
1
1
Order By: Relevance
“…In the past decade, evolutionary ecology studies have documented many cases of evolution occurring on ecological time-scales [1][2][3], while community genetics research has demonstrated that the genetic identity of a focal species can affect associated community members and ecosystem processes [18,30,31]. Here, we integrate concepts from these two fields and show that rapid evolutionary responses to a novel stress associated with climate change have community-wide consequences for associated species.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, evolutionary ecology studies have documented many cases of evolution occurring on ecological time-scales [1][2][3], while community genetics research has demonstrated that the genetic identity of a focal species can affect associated community members and ecosystem processes [18,30,31]. Here, we integrate concepts from these two fields and show that rapid evolutionary responses to a novel stress associated with climate change have community-wide consequences for associated species.…”
Section: Discussionmentioning
confidence: 99%
“…v www.esajournals.org Overall, our work responds to recent appeals for comparisons of the importance of genetic variation and genotypic diversity relative to other ecological factors (Hughes et al 2008, Hersch-Green et al 2011). In the S. altissima system, the effects of genetic variation were greater than that of nutrient enrichment, but this is not always the case (Orians and Fritz 1996, Mutikainen et al 2000, Stiling and Bowdish 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Host-plant genotype identity and genotypic diversity account for some of the variance in the communities associated with them, but the relative importance of genetic variation and genotypic diversity compared to other ecological factors, such as environmental heterogeneity, is only beginning to be understood (Hughes et al 2008, Hersch-Green et al 2011. One key environmental factor for plants and their associated floral visitors is soil nutrient availability, as nutrients can vary considerably at a local level and are known to influence flower production and bloom duration (e.g., Campbell and Halama 1993, Asikainen and Mutikainen 2005, Munoz et al 2005, Burkle and Irwin 2009a.…”
Section: Introductionmentioning
confidence: 99%
“…Fagaceae species are dominant species of most temperate forest ecosystems and are drivers of terrestrial biodiversity. Interactions between trees and their associated species (mammals, fungi, and pathogens) can be tackled via gene-gene (or gene-species) interactions once candidate genes are known (Hersch-Green et al 2011). & Breeding and genetic improvement.…”
Section: Resultsmentioning
confidence: 99%